Synthesis and Applications of Porphyrin-Biomacromolecule Conjugates - Pathak, Pravin; Zarandi, Mohammad Amin; Zhou, Xiao; Jayawickramarajah, Janarthanan (Frontiers in Chemistry, 2021)
With potential applications in materials and especially in light-responsive biomedicine that targets cancer tissue selectively, much research has focused on developing covalent conjugation techniques to tether porphyrinoid units to various biomacromolecules. This review details the key synthetic approaches that have been employed in the recent decades to conjugate porphyrinoids with oligonucleotides (ONs) and peptides/proteins. In addition, we provide succinct discussions on the subsequent applications of such hybrid systems and also give a brief overview of the rapidly progressing field of porphyrin-antibody conjugates. Since nucleic acid and peptide systems vary in structure, connectivity, functional group availability and placement, as well as stability and solubility, tailored synthetic approaches are needed for conjugating to each of these biomacromolecule types. In terms of tethering to ONs, porphyrins are typically attached by employing bioorthogonal chemistry (e.g., using phosphoramidites) that drive solid-phase ON synthesis or by conducting post-synthesis modifications and subsequent reactions (such as amide couplings, hydrazide-carbonyl reactions, and click chemistry). In contrast, peptides and proteins are typically conjugated to porphyrinoids using their native functional groups, especially the thiol and amine side chains. However, bioorthogonal reactions (e.g., Staudinger ligations, and copper or strain promoted alkyne-azide cycloadditions) that utilize de novo introduced functional groups onto peptides/proteins have seen vigorous development, especially for site-specific peptide-porphyrin tethering. While the ON-porphyrin conjugates have largely been explored for programmed nanostructure self-assembly and artificial light-harvesting applications, there are some reports of ON-porphyrin systems targeting clinically translational applications (e.g., antimicrobial biomaterials and site-specific nucleic acid cleavage). Conjugates of porphyrins with proteinaceous moieties, on the other hand, have been predominantly used for therapeutic and diagnostic applications (especially in PDT, PACT, PTT). The advancement of the field of porphyrinoid-bioconjugation chemistry from basic academic research to more clinically targeted applications require continuous fine-tuning in terms of synthetic strategies and hence there will continue to be much exciting work on porphyrinoid-biomacromolecule conjugation.